Practical spectroscopy in agriculture and food science - Posudin, I͡U. I. (I͡Uriĭ Ivanovych) (Science Publishers, 2007)
This monograph introduces the students and specialists of agricultural and food science to the fundamentals of optical spectroscopy, main principles of modern spectroscopic instrumentation, advantages and practical applications of spectroscopic methods to investigation of agricultural objects such as milk and dairy products, eggs, honey, animal hair, and agronomic plants.